Washington Warning Area Map 1 - Evacuation zone and routes (1959) (U.S. Government Printing Office Washington, D.C., 1959)
Front side shows street map of Washington D.C. and surrounding area with evacuation routes. Back side shows wider area to include Southern Maryland and Northern Virginia